(untitled) (Global Journal of Human-Social Science, 2024)
The COVID-19 pandemic prompted the government of Nepal to institute a series of lockdowns from March 24 2020 significantly affecting the livelihoods of its citizens This study explores stratified livelihoods during Pandemic lockdowns in Nepal and of these measures uncovering nuanced and diverse experiences across different strata of Nepali society Therefore utilizing a qualitative research approach the study employs primary and secondary data collection methods such as observations and case studies and analyses the data through content analysis techniques The findings reveal a spectrum of impacts ranging from individuals finding solace and familial bonding during the lockdown equating it to a period of celebration to those experiencing severe hardships These hardships included undertaking long-distance travel on foot without adequate sustenance and facing limited access to medical care The diverse experiences observed align to some extent with the theoretical frameworks of Marx and Weber showcasing the varied socio-economic repercussions of the lockdown measures This research sheds light on the complex dynamics of pandemic interventions on livelihoods within the Nepali context It provides valuable insights to understand and mitigate the multifaceted impacts of such measures on various societal layers